PENERIMAAN KAUM HOMOSEKSUAL DALAM SEKTOR KERJA FORMAL DI DENPASAR DAN BADUNG - Findiarni, Natasha Althea; Bagus Suka Arjawa, I Gusti Putu; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study aims to examine the acceptance of homosexuals and the strategy they use to survive in the formal sector job in Denpasar and Badung. This study uses a qualitative approach. The theory used in this research is the post-colonialism theory from Homi K Bhabha with Mimicry concept. The results showed how the acceptance of homosexuals is influenced by the narrative that has been built by the public about heteronormative. That put the homosexual into the subaltern group. This situation requires homosexual group to use a strategy so that they can be accepted by hiding and imitating. This act of imitation that makes them to be the almost the same subject but still not exactly the same as the self they are imitating, which is Bhabha called as Mimicry. Keywords: Homosexual, Mimicry, Subaltern, Heteronormative, Formal sector job